Commentary on the sentence of the Regional Court – October 23, 2015, ref. No. III K 128/15 - Witczak, Karolina (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
The commentary on the sentence of the Regional Court – October 23, 2015 concerned the issue of the fixation of the image of the naked person, who was a minor under the age of 15. The author of the essay compared legally protected interests on the grounds of art. 191a § 1 of the Penal Code and art. 202 § 4 of the Penal Code. Moreover, the feature of the “image of the naked person” on account of the factual situation was raised. Finally, the problem of inducing deceit of an image of the adolescent by the perpetrator, was discussed.